Naps Do Not Change Delay Discounting Behavior in Young Adults - O’Connor, Sean; Sonni, Akshata; Karmarkar, Uma; Spencer, Rebecca M. C. (Frontiers in Psychology, 2018)
When offered a choice of $40 today or $50 later, many would choose the immediate reward over the greater delayed reward. Such behavior is a result of future gains being discounted such that their value is rendered less than that of the immediate gain. Extreme discounting behaviors are associated with impulsivity and addiction. Given recent evidence of sleep's role in decision making, we tested the hypothesis that sleep would reduce delayed discounting behavior. Twenty young adults (M = 20.19 yrs, SD = 0.98 yrs; 6 males) performed a hypothetical delay discounting task, making a series of choices between an immediate reward (from $0 to $50) or a larger reward ($50) available at a delay of 2, 4, 8, 14 or 22 weeks. Participants performed the task before and after a mid-day nap, and before and after an equivalent interval of wake (within subject, order counterbalanced, wake and sleep conditions separated by 1 week). As expected, indifference points decreased with longer delays both prior to and following the nap/wake interval. However, the impact of a nap interval on discounting did not differ from the impact of a wake interval. Thus, while sleep has been shown to play an active role in some financial decision-making tasks, a nap is not sufficient to change delay discounting behavior.